ANALISIS PENGAWASAN LOGISTIK PRODUK AQUA UKURAN 330ML PADA CV. DLU’X RESTO SAMARINDA - Mardiana, Ali Masuhud, H. Mulyadi Syp (EKONOMIA, 2016)
The problem in this research is "Are Determination Against Aqua Products Logistics Control 330ml sizes on CV. DLux Resto has been optimized? "This study aims to determine the amount of inventory on the CV aqua 330ml sizes. Dlu'x Resto in Samarinda.Formulation of the problem in this study is whether the determination of the logistical monitoring product inventory aqua 330ml sizes that have been carried out on the CV. Dlu'x Resto Samarinda already performed optimally.The hypothesis in this study is: "Suspected determination to stock up on surveillance logistics 330ml sizes aqua products made by CV.Dlu'x Resto Samarinda not optimal".Basic theory used in this study are: Management consisting of a Definition of Management, Scope Management Production and Operations, Function Production Management and Operations, Understanding Monitoring, Understanding Logistics, Inventory Management, Function Inventory, Interest Inventory, Inventory Control, Interest Inventory Control, Cost Inventory, Forecasting, Economic Order Quantity (EOQ), Safety Stock, Reorder Point, Lead Time.The analysis tool used is particular theory of inventory management using 2001 data, inventory aqua 330ml size is calculated using the Model Economic Order Quantity (EOQ) as an analytical tool. Economic Order Quantity (EOQ) is a model that involves the procurement of raw materials or stock in a company. Every industrial company certainly require raw materials for smooth business processes, the raw materials obtained from suppliers with a certain calculation. By using the calculations of course, a company can economically regularly determine how and how much material must be provided. Irregularities scheduling will impact on inventory costs by stacking in warehouse inventory. Thus, management or control of raw materials is important and slah one thing can save the company money.Thus the hypothesis presented earlier stating that inventories 330ml aqua as the product on a CV. Dlu'x Resto in Samarinda not provide optimal inventory costs